Estilos de afrontamiento al estrés durante la pandemia por covid-19 en estudiantes del Instituto Superior Pedagógico Privado Bernabé Cobo - Cusco, 2021 - Tongombol Rodriguez, Evelyn Yaniba (2022)
Objective: To identify the styles of coping with stress during the COVID-19 pandemic in students of the Instituto Superior Pedagogic Privado Bernabé Cobo - Cusco, 2021 Methodology: Basic type study, descriptive level and non-experimental cross-sectional design. The population consisted of 100 students and the sample of 80 students. The data collection technique was the survey and the instrument was the Coping with Stress Questionnaire (COPE). The information processing was carried out through the use of descriptive statistics. Results: The results show that the majority use the style based on the problem according to the circumstances in 88.8%, followed by the style directed to emotion in 72.5% and rarely the style based on avoidance in 50.0%. Regarding the dimension styles based on the problem, the styles frequently used are: Postponement of coping with 46.3%, Active coping 33.8% and Planning 33.0%. In the emotion-based styles dimension, the styles frequently used are: Go to religion 41.3%, Search for emotional support 25.0% and Analysis of emotions 23.8%. And in the dimension styles based on avoidance, the most used styles are: Distraction 36.3%, Denial 20.0% and Inappropriate behaviors 6.3%. Conclusions: It has been identified that the coping style based on the problem is the one most used by the students of the Instituto Superior Pedagogic Privado Bernabé Cobo - Cusco, 2021 Keywords: Stress coping styles, students